Effectiveness of music therapy as an aid to neurorestoration of children with severe neurological disorders - Bringas, Maria L.; Zaldivar, Marilyn; Rojas, Pedro A.; Martinez-Montes, Karelia; Chongo, Dora M.; Ortega, Maria A.; Galvizu, Reynaldo; Perez, Alba E.; Morales, Lilia M.; Maragoto, Carlos; Vera, Hector; Galan, Lidice; et al. (Frontiers in Neuroscience, 2015)
This study was a two-armed parallel group design aimed at testing real world effectiveness of a music therapy (MT) intervention for children with severe neurological disorders. The control group received only the standard neurorestoration program and the experimental group received an additional MT “Auditory Attention plus Communication (ACC) protocol” just before the usual occupational and speech therapy. Multivariate Item Response Theory (MIRT) identified a neuropsychological status-latent variable manifested in all children and which exhibited highly significant changes only in the experimental group. Changes in brain plasticity also occurred in the experimental group, as evidenced using a Mismatch Event Related paradigm which revealed significant post intervention positive responses in the latency range between 308 and 400 ms in frontal regions. LORETA EEG source analysis identified prefrontal and midcingulate regions as differentially activated by the MT in the experimental group. Taken together, our results showing improved attention and communication as well as changes in brain plasticity in children with severe neurological impairments, highlight/comfort the importance of MT for the rehabilitation of patients across a wide range of dysfunctions.